Effects of carbon dioxide addition to fuel on flame radiation fraction in propane diffusion flames. (1st March 2021) - Dou, Yuling; Liu, Haiqiang; Liu, Bin; Zhang, Yu; Liu, Yongqiang; Cheng, Xiaozhang; Tao, Changfa
Abstract: The flame radiation fraction of the turbulent jet diffusion flame of propane and carbon dioxide mixed gas was studied under the ambient temperature of 300 K and the pressure of 1 bar. The diameters of the nozzle were 2, 3, and 4 mm. Different flow rates of propane and carbon dioxide were controlled to obtain different concentration ratios. The results showed that for a given heat release rate, the flame heat radiation fraction decreases with increasing the concentration of carbon dioxide in the gas mixture. Theories of soot formation and laminar flame speed were used to explain the evolution of the radiation fraction under different volume fractions of carbon dioxide. A correlation model about the relationship among the radiation fraction, heat release rate, and fuel equivalent ratio was proposed. Highlights: Effect of carbon dioxide concentration on radiation fraction of jet flame revealed. The flame radiation fraction is inverse proportional to carbon dioxide volume rate. Correlation for flame radiation fraction established based on laminar flame speed.